Learning The Periodic System Elements With Microsoft Teams To Improve Learning Independence - Romadhona, Galih Putri; Dwiningsih, Kusumawati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
Abstract: In supporting the implementation of hybrid learning during the pandemic Covid-19, it is necessary to use a learning media that is expected to help realize effective and can make it easier for students to understand learning material. One of the learning media that can be used is Microsoft Teams. Under these conditions, the intensity of face-to-face meetings between students and teachers has not fully returned. Therefore, students must be able to learn independently. This study aims to improve student learning independence by using Microsoft Teams on the material of the periodic system of elements. The research design used is a one group pretest posttest design. The results showed 1) the implementation of learning using Microsoft Teams was very well done, 2) teachers have carried out effective learning management 3) the percentage of relevant student activities is 96%. 4) students' learning independence has increased, 5) the majority of students experience increased learning independence . 5) students gave a positive response on the use of Microsoft Teams. It can be concluded that the use of Microsoft Teams can improve student learning independence. Keywords: Microsoft Teams; learning independence; hybrid learning; Covid-i9 Abstrak: Dalam mendukung kelancaran pelaksanaan pembelajaran hybrid di masa pandemic Covid-19 diperlukan adanya penggunaan suatu media pembelajaran yang diharapkan dapat membantu mewujudkan pembelajaran yang efektiv dan dapat mempermudah peserta didik dalam memahami materi pembelajaran. Salah satu media pembelajaran yang dapat digunakan adalah platform Microsoft Teams. Dalam kondisi seperti ini, intensitas tatap muka antara siswa dengan guru masih belum kembali sepenuhnya. Oleh karena itu, siswa perlu bisa belajar dengan mandiri. Penelitian ini bertujuan untuk meningkatkan kemandirian belajar siswa dengan menggunakan Microsoft Teams pada materi system periodic unsur. Desain peneleitian yang digunakan adalah one group pretest posttest design. Hasil penelitian menunjukkan bahwa 1) keterlaksanaan pembelajaran menggunakan Microsoft Teams terlaksana dengan sangat baik, 2) guru telah melakukan pengelolaan pembelajaran yang efektif, 3) persentase aktivitas siswa yang relevan sebesar 96 %. 4) kemandirian belajar siswa mengalami peningkatan, 5) hasil pengamatan kemandirian terhadap masing-masing siswa menunjukkan mayoritas siswa telah mengalami peningkatan kemandirian belajar, 5) siswa memberikan respon positif terhadap penggunaan Microsoft Teams. Berdasarkan hasil penelitian dapat disimpulkan bahwa penggunaan Microsoft Teams dapat meningkatkan kemandirian belajar siswa. Kata kunci: Microsoft Teams; kemandirian belajar; pembelajaran hybrid; Covid-19